Competitive interactions and resource partitioning between northern spotted owls and barred owls in western Oregon. Issue 185 (February 2014) - Wiens, J. David; Anthony, Robert G.; Forsman, Eric D.
ABSTRACT: The federally threatened northern spotted owl ( Strix occidentalis caurina ) is the focus of intensive conservation efforts that have led to much forested land being reserved as habitat for the owl and associated wildlife species throughout the Pacific Northwest of the United States. Recently, however, a relatively new threat to spotted owls has emerged in the form of an invasive competitor: the congeneric barred owl ( S. varia ). As barred owls have rapidly expanded their populations into the entire range of the northern spotted owl, mounting evidence indicates that they are displacing, hybridizing with, and even killing spotted owls. The range expansion by barred owls into western North America has made an already complex conservation issue even more contentious, and a lack of information on the ecological relationships between the 2 species has hampered recovery efforts for northern spotted owls. We investigated spatial relationships, habitat use, diets, survival, and reproduction of sympatric spotted owls and barred owls in western Oregon, USA, during 2007–2009. Our overall objective was to determine the potential for and possible consequences of competition for space, habitat, and food between these previously allopatric owl species. Our study included 29 spotted owls and 28 barred owls that were radio‐marked in 36 neighboring territories and monitored over a 24‐month period. Based on repeated surveys of both species, the number of territories occupied by pairs of barred owls in the 745‐km 2 study area (82) greatly outnumbered those occupied by pairs of spotted owls (15). Estimates of mean size of home ranges and core‐use areas of spotted owls (1, 843 ha and 305 ha, respectively) were 2–4 times larger than those of barred owls (581 ha and 188 ha, respectively). Individual spotted and barred owls in adjacent territories often had overlapping home ranges, but interspecific space sharing was largely restricted to broader foraging areas in the home range with minimal spatial overlap among core‐use areas. We used an information‐theoretic approach to rank discrete‐choice models representing alternative hypotheses about the influence of forest conditions, topography, and interspecific interactions on species‐specific patterns of nighttime resource selection. Spotted owls spent a disproportionate amount of time foraging on steep slopes in ravines dominated by old (>120 yr) conifer trees. Barred owls used available forest types more evenly than spotted owls, and were most strongly associated with patches of large hardwood and conifer trees that occupied relatively flat areas along streams. Spotted and barred owls differed in the relative use of old conifer forest (greater for spotted owls) and slope conditions (steeper slopes for spotted owls), but we found no evidence that the 2 species differed in their use of young, mature, and riparian‐hardwood forest types. Mean overlap in proportional use of different forest types between individual spotted owls and barred owls in adjacent territories was 81% (range = 30–99%). The best model of habitat use for spotted owls indicated that the relative probability of a location being used was substantially reduced if the location was within or in close proximity to a core‐use area of a barred owl. We used pellet analysis and measures of food‐niche overlap to determine the potential for dietary competition between spatially associated pairs of spotted owls and barred owls. We identified 1, 223 prey items from 15 territories occupied by spotted owls and 4, 299 prey items from 24 territories occupied by barred owls. Diets of both species were dominated by nocturnal mammals, but diets of barred owls included many terrestrial, aquatic, and diurnal prey species that were rare or absent in diets of spotted owls. Northern flying squirrels ( Glaucomys sabrinus ), woodrats ( Neotoma fuscipes, N. cinerea ), and lagomorphs ( Lepus americanus, Sylvilagus bachmani ) were primary prey for both owl species, accounting for 81% and 49% of total dietary biomass for spotted owls and barred owls, respectively. Mean dietary overlap between pairs of spotted and barred owls in adjacent territories was moderate (42%; range = 28–70%). Barred owls displayed demographic superiority over spotted owls; annual survival probability of spotted owls from known‐fate analyses (0.81, SE = 0.05) was lower than that of barred owls (0.92, SE = 0.04), and pairs of barred owls produced an average of 4.4 times more young than pairs of spotted owls over a 3‐year period. We found a strong, positive relationship between seasonal (6‐month) survival probabilities of both species and the proportion of old (>120 yr) conifer forest within individual home ranges, which suggested that availability of old forest was a potential limiting factor in the competitive relationship between these 2 species. The annual number of young produced by spotted owls increased linearly with increasing distance from a territory center of a pair of barred owls, and all spotted owls that attempted to nest within 1.5 km of a nest used by barred owls failed to successfully produce young. We identified strong associations between the presence of barred owls and the behavior and fitness potential of spotted owls, as shown by changes in movements, habitat use, and reproductive output of spotted owls exposed to different levels of spatial overlap with territorial barred owls. When viewed collectively, our results support the hypothesis that interference competition with barred owls for territorial space can constrain the availability of critical resources required for successful recruitment and reproduction of spotted owls. Availability of old forests and associated prey species appeared to be the most strongly limiting factors in the competitive relationship between these species, indicating that further loss of these conditions can lead to increases in competitive pressure. Our findings have broad implications for the conservation of spotted owls, as they suggest that spatial heterogeneity in vital rates may not arise solely because of differences among territories in the quality or abundance of forest habitat, but also because of the spatial distribution of a newly established competitor. Experimental removal of barred owls could be used to test this hypothesis and determine whether localized control of barred owl numbers is an ecologically practical and socio‐politically acceptable management tool to consider in conservation strategies for spotted owls. © 2013 The Wildlife Society